PENGARUH KADAR AIR, DOSIS DAN LAMA PENGENDAPAN KOAGULAN SERBUK BIJI KELOR SEBAGAI ALTERNATIF PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU - Ayu Ridaniati Bangun, Siti Aminah, Rudi Anas Hutahaean, M. Yusuf Ritonga (Jurnal Teknik Kimia USU, 2013)
Liquid waste industrial of wheys contain very high organic materials. Organic compounds in the effluent are proteins, carbohydrates, fats and oils. Based on the results of field studies on Industry Hall of liquid waste industrial characteristics of whey in Medan, it is known that liquid waste industrial of wheys contain average BOD (4583 mg/l), COD (7050 mg/l), TSS (4743 mg/l ) and oil or fat (26 mg/l ) at pH 6.1. Therefore, the whey waste water must be treated before it is discharged into the environment to reduce the contaminants that accompany the waste. One alternative that can be used as a coagulant is moringa seed powder. This study used of moringa seed powder with a water content of 7 %. Variations of coagulant dosage which are used 2000, 3000, 4000, 5000 mg/200 ml liquid waste industrial of whey, coagulant particle size 50 and 70 mesh with the initial pH about 4. The optimum deposition time is obtained 60 minutes with 77.43 % reduction in turbidity, TSS 90.32 %, and 63.26 % COD in 5000 mg/200 ml dosage of coagulant and coagulant particle size of 70 mesh with the final pH about 4, it can be concluded that moringa seeds can be used as an effective coagulant because the reductions were obtained over 50 %.Keywords : liquid waste industrial of whey, moringa seed powder, turbidity, TSS, COD